Biological Tests of Chromium-cobalt Alloy Coated with Zirconium Nitride and Titanium Nitride - J. Vaněk; P. Prachár; S. Bartáková; V. Březina; L. Freyburg (Czech Dental Chamber, 2005)
It is well established in recent clinical stomatology that the materials used routinely in oral cavity, mucosa, and bridges constructions have proper mechanical and physical characteristics. The materials are ideal from technological point of view and it is easy to work with them in clinical practice. Their processing and surface finishing is easy. The materials show high biocompatibility when used in gingival and mucosal surfaces. In a jaw, the contact of implant materials with bone tissue and required osseointegration represent more complex and demanding issue than in soft tissues. In bone tissue, there is a necessity to use the materials exhibiting a high level of bioactivity. Within the frame of a long-term research project, we tested a modification of material routinely used in stomatological practice. A chromium-cobalt alloy was coated with titanium nitrate or zirconium nitrate. The two above-specified surface layers were tested for a prospective application in dental implantology. The results of standard biotests demonstrated a biocompatibility sufficient for the requirements of dental implantology.